A survey of the apes in the Dzanga-Ndoki National Park, Central African Republic: a comparison between the census and survey methods of estimating the gorilla (Gorilla gorilla gorilla) and chimpanzee (Pan troglodytes) nest group density - Blom, A.; Almaši, A.; Heitkönig, I. M. A.; Kpanou, J.-B.; Prins, H. H. T. (African journal of ecology, 2001)
A survey of apes was carried out between October 1996 and May 1997 in the Dzanga sector of the Dzanga‐Ndoki National Park, Central African Republic (CAR), to estimate gorilla (Gorilla gorilla gorilla) and chimpanzee (Pan troglodytes) densities. The density estimates were based on nest counts. The strip transect census and the line transect survey method (Standing Crop Nest Count) were used to estimate the gorilla nest group density. The strip transect has been most commonly used to date. It assumes that all nest groups within the width of the strip are detected, but as this assumption is easily violated in the dense tropical rain forest, the line transect survey was also used. In this method, only the nest groups on the transect line itself should be detected. This method proved to be an adequate and easy technique for estimating animal densities in dense vegetation. The gorilla density of 1.6 individuals km−2 (line transect survey method) found for the Dzanga sector is one of the highest densities ever reported in the literature for the Western lowland gorilla. The density estimate for chimpanzees was 0.16 individuals km−2 (census method). The results of this study confirm the importance of the Dzanga‐Ndoki National Park for primate conservation. Résumé Entre octobre 1996 et mai 1997, on a étudié les grands singes du secteur de Dzanga dans le Parc National de Dzanga‐Ndoki, en République Centrafricaine (RCA), pour évaluer les densités de gorilles (Gorilla gorilla gorilla) et de chimpanzés (Pan troglodytes). Les estimations de densité se basaient sur le comptage des nids. On a utilisé le recensement par bande transect et la méthode de contrôle par transect linéaire (comptage réel des nids) pour estimer la densité des groupes de nids de gorilles. C'est la bande transect qui est la plus communément utilisée à ce jour. Cela suppose que l'on détecte tous les groupes de nids inclus dans la largeur de la bande, mais comme cette supposition est facilement mise en défaut dans la forêt tropicale humide dense, on a aussi utilisé la méthode des transects en ligne. Avec cette méthode, seuls les groupes de nids qui sont sur la ligne de transect doivent être détectés. Cette méthode s'est révélée une technique adéquate et facile pour estimer les densités animales dans la végétation dense. La densité des gorilles (1,6 individus / km2) relevée pour le secteur de Dzanga est une des plus élevées jamais reportées dans la littérature pour le Gorille de plaine occidental. On a estimé la densité des chimpanzés à 0,16 individus / km2 (par la méthode de recensement). Les résultats de cette étude confirment l'importance du Parc National de Dzanga‐Ndoki pour la conservation des primates.